ITG turbulence in gyrokinetic simulations of high collisionality spherical tokamak plasmas - N. Kumar; G. Avdeeva; J. Candy; M. Reynolds; E. Belli; C.P. McNally (Nuclear Fusion, 2025)
This paper presents a first detailed gyrokinetic analysis with the goal of understanding the dominant turbulent transport mechanisms and identifying the micro-instabilities present in small-aspect-ratio plasmas in the PI3 device, developed as magnetized target fusion targets. These plasmas are characterized by low temperatures and high collisionality compared to standard tokamaks. Linear and ion-scale nonlinear gyrokinetic flux tube simulations are performed at radial positions $r/a = 0.60$ , 0.65, 0.70, and 0.75 using the gyrokinetic code CGYRO (Candy et al 2016 J. Comput. Phys. 324 73). Linear stability analysis finds that ion temperature gradient (ITG) modes dominate at ion scales, while electron-temperature gradient modes dominate at electron scales. Trapped electron modes (TEMs) remain stable due to high collisionality. At very low $k_yρ_s$ , microtearing modes (MTMs) are linearly unstable at all radial locations. In the nonlinear regime, turbulence is driven primarily by ITG modes, which dominate both ion and electron energy fluxes. Interestingly, although MTMs are linearly unstable, they are suppressed in the nonlinear phase, except for a small, negative magnetic flutter contribution at the outer radius ( $r/a = 0.75$ ) that slightly reduces the total electron energy flux. The sensitivity of these instabilities to key plasma parameters is investigated. High collisionality significantly reduces nonlinear turbulent fluxes, and lowering collisionality results in a stronger flux increase than an equivalent increase in plasma beta does. Increasing the $T_\mathrm i/T_\mathrm e$ ratio in the linear analysis stabilizes ITG modes, while simultaneously destabilizing long-wavelength MTMs. Finally, turbulent energy fluxes are compared to neoclassical transport values simulated using NEO (Belli et al 2008 Plasma Phys. Control. Fusion 50 095010), showing transport is anomalous at all radii.